Phase 1 Study of High-Specific-Activity I-131 MIBG for Metastatic and/or Recurrent Pheochromocytoma or Paraganglioma - Noto, Richard B; Pryma, Daniel A; Jensen, Jessica; Lin, Tess; Stambler, Nancy; Strack, Thomas; Wong, Vivien; Goldsmith, Stanley J (The journal of clinical endocrinology and metabolism, 2018)
No therapies are approved for the treatment of metastatic and/or recurrent pheochromocytoma or paraganglioma (PPGL) in the United States. To determine the maximum tolerated dose (MTD) of high-specific-activity I-131 meta-iodobenzylguanidine (MIBG) for the treatment of metastatic and/or recurrent PPGL. Phase 1, dose-escalating study to determine the MTD via a standard 3 + 3 design, escalating by 37 MBq/kg starting at 222 MBq/kg. Three centers. Twenty-one patients were eligible, received study drug, and were evaluable for MTD, response, and toxicity. Open-label use of high-specific-activity I-131 MIBG therapy. Dose-limiting toxicities, adverse events, radiation absorbed dose estimates, radiographic tumor response, biochemical response, and survival. The MTD was determined to be 296 MBq/kg on the basis of two observed dose-limiting toxicities at the next dose level. The highest mean radiation absorbed dose estimates were in the thyroid and lower large intestinal wall (each 1.2 mGy/MBq). Response was evaluated by total administered activity: four patients (19%), all of whom received >18.5 GBq of study drug, had radiographic tumor responses of partial response by Response Evaluation Criteria in Solid Tumors. Best biochemical responses (complete or partial response) for serum chromogranin A and total metanephrines were observed in 80% and 64% of patients, respectively. Overall survival was 85.7% at 1 year and 61.9% at 2 years after treatment. The majority (84%) of adverse events were considered mild or moderate in severity. These findings support further development of high-specific-activity I-131 MIBG for the treatment of metastatic and/or recurrent PPGL at an MTD of 296 MBq/kg.